Sugar Cane Farmer’S Social Capital And Partnership In PG. Madukismo - Resna Trimerani; Ismiasih Ismiasih (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose : The aim of this research is to determine the partnership system that operates in PG. Madukismo and knowing the social capital in the partnership. Methodology : The research method used was descriptive qualitative, while the sampling method used was purposive sampling with a total sample of 30 sugar cane farmers. Results : The research results show that the social capital found in partnerships, namely trust, social norms (reciprocity) and social networks, has an average value of 2.94. Findings : This figure shows that the three elements of social capital are included in the high category in the partnership between sugar cane farmers and PG. Madukismo. Novelty : The partnership system found in PG. Madukismo is the People's Sugarcane Partnership System (TRK) and the Mandiri People's Sugarcane Partnership System (TRM). Originality: This study reveals that social capital in the form of trust, social norms and social networks are very instrumental in the partnership of sugarcane farmers with PG. Madukismo. Conclusion: The partnership system found in PG. Madukismo is the People's Sugarcane Partnership System (TRK) and the Mandiri People's Sugarcane Partnership System (TRM). While the social capital that plays a role in the partnership includes trust, norms contained in the form of reciprocity and social networks. Type of paper : Empirical Research Paper